Therapeutic Modulation of Plasmacytoid Dendritic Cells in Experimental Arthritis. Issue 11 (27th October 2017) - Nehmar, Ramzi; Alsaleh, Ghada; Voisin, Benjamin; Flacher, Vincent; Mariotte, Alexandre; Saferding, Victoria; Puchner, Antonia; Niederreiter, Birgit; Vandamme, Thierry; Schabbauer, Gernot; Kastner, Philippe; Chan, Susan; et al.
Abstract : Objective: The role of plasmacytoid dendritic cells (PDCs) and type I interferons (IFNs) in rheumatoid arthritis (RA) remains a subject of controversy. This study was undertaken to explore the contribution of PDCs and type I IFNs to RA pathogenesis using various animal models of PDC depletion and to monitor the effect of localized PDC recruitment and activation on joint inflammation and bone damage. Methods: Mice with K/BxN serum–induced arthritis, collagen‐induced arthritis, and human tumor necrosis factor transgene insertion were studied. Symptoms were evaluated by visual scoring, quantification of paw swelling, determination of cytokine levels by enzyme‐linked immunosorbent assay, and histologic analysis. Imiquimod‐dependent therapeutic effects were monitored by transcriptome analysis (using quantitative reverse transcriptase–polymerase chain reaction) and flow cytometric analysis of the periarticular tissue. Results: PDC‐deficient mice showed exacerbation of inflammatory and arthritis symptoms after arthritogenic serum transfer. In contrast, enhancing PDC recruitment and activation to arthritic joints by topical application of the Toll‐like receptor 7 (TLR‐7) agonist imiquimod significantly ameliorated arthritis in various mouse models. Imiquimod induced an IFN signature and led to reduced infiltration of inflammatory cells. Conclusion: The therapeutic effects of imiquimod on joint inflammation and bone destruction are dependent on TLR‐7 sensing by PDCs and type I IFN signaling. Our findings indicate that local recruitment and activation of PDCs represents an attractive therapeutic opportunity for RA patients.